2012
DOI: 10.1007/s00586-012-2220-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transnasal odontoid resection to decompress the bulbo-medullary junction: a reliable anterior minimally invasive technique without posterior fusion

Abstract: Compared with the standard transoral technique, the EEA provides the same good exposure but with potentially less complications. The preservation of the anterior C1 arch can contribute to avoid cranial settling and posterior fusion with its related risk of subaxial instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 24 publications
0
49
0
2
Order By: Relevance
“…A linear incision in the mucosa has been suggested as preferable and both are viable in our hands. 12 Finally, we found that in spite of achieving an adequate anatomical decompression of the CMJ as well as symptomatic relief, it was not uncommon to find a small shell of residual odontoid on the left side, seen in 43% of patients. This finding is puzzling since a right-sided approach should direct the surgeon more to the left.…”
Section: -2830mentioning
confidence: 82%
See 2 more Smart Citations
“…A linear incision in the mucosa has been suggested as preferable and both are viable in our hands. 12 Finally, we found that in spite of achieving an adequate anatomical decompression of the CMJ as well as symptomatic relief, it was not uncommon to find a small shell of residual odontoid on the left side, seen in 43% of patients. This finding is puzzling since a right-sided approach should direct the surgeon more to the left.…”
Section: -2830mentioning
confidence: 82%
“…20 Although we performed fusion in all patients in this series who underwent an odontoidectomy, rather than just a biopsy, prior reports have claimed that fusion may not be necessary after endonasal odontoidectomy. 12 This was attributed to a reduction in instability due to the minimally invasive endonasal approach and preserving the C-1 arch. 12 In our series, we have not been able to remove the odontoid adequately without removing the anterior ring of C-1.…”
Section: -2830mentioning
confidence: 99%
See 1 more Smart Citation
“…25,47,55 Although these extended approaches can lead to significant enhancement of the surgical exposure, they also significantly increase surgical complexity and the depth of the operative corridor, rates of morbidities such as infections from bacterial oral flora, velopharyngeal insufficiency, hypernasal speech, nasal regurgitation, soft palate dehiscence, tongue edema, and necrosis, and the potential need for tracheotomy and nasogastric feeding tube, resulting in a longer hospital recovery time. 10,37,41,45 In the last decade, some minimally invasive endoscopic approaches, such as the EEA, 7,8,11,18,19,[21][22][23][24]26,27,29,30,[33][34][35]40,44,51 the ETA, 16,17 a combined EEA/ETA with or without the assistance of robotics, 12,13,31,32,50,54 and a transcervical approach, 53 have been adopted to address CVJ pathology. The growing number of publications in the last decade shows that the EEA can be an excellent minimal-access alternative to traditional transoral surgery and offers certain anatomical advantages.…”
Section: Discussionmentioning
confidence: 99%
“…All these publications highlight the benefits of endoscopic endonasal odontoidectomy as a safe, effective, and welltolerated technique. 7,8,11,18,19,[21][22][23][24]26,27,29,30,[33][34][35]40,44,51 The main advantages of the EEA over the traditional microscopic approaches are the location of the incision (in the nasopharynx rather than the oropharynx) and the wider, closer, and brighter view provided by the endoscope.…”
Section: Discussionmentioning
confidence: 99%